Course Syllabus: Developing the Social Education Information Network - KOVALEV, Evgeny; SALEH, Hadi (Journal of Education, Technology and Computer Science, 2014)
In paper is description: on-line education course Developing the Social Education Information Network. Purpose: to acquire competence in the selection and analysis of platform to deploy the university’s social network, to deploy solutions on selected platform, to elaborate the educational content of the network and to arrange for interaction between the parties to the education process. With the above purpose implemented, the target users will be able to operate the university’s shared educationinformation space. Target users: university students, academic and IT personnel.